PERUBAHAN SISTEM PRODUKSI PERTANIAN LADA PADA MASA KOMPENI INGGRIS DI BENGKULU TAHUN 1800-1825 - , LAILATUSYSYUKRIYAH; , Nur âAini Setiawati Ph. D. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study discusses about the transformation of production system of pepper plantation in Bencoolen during British East India Company 1800-1825, how is pepper production system has been changed in these periods?, what is the factors of Companyâs failure in developed pepper production system in 1800-1817, and what is the implication of the policy alteration of pepper plantation production system to the Company?. This study uses the methods of history (historical method) by using three stages: heuristic, source critical, and interpretation (explanation). The main of written sources are used in the form archive, document, and report that obtained from Indonesia National Archives. The secondary of written sources are used in the form literature and journals from the any other libraries. Based on the studies, it can be concluded first, the production system alteration of pepper plantation in 1800-1825 was resulted the transformation from trade monopoly under Companyâs power to self-supporting other cash crops. Two, the unsuccessful of British East India Company authority in 1800-1817 on the pepper production system had been caused by mismanagement bureaucracy system, corruption in British East India Companyâs administration and the local authority, monopolistic practices, geography obstacles, and the labor problems. Third, the Company was beginning the new strategic into agricultural system that have been changing the value of pepper production from primary to secondary commodity.